Polyamic acid solution
The polyamic acid solution with specific terminal structures addresses the issue of viscosity changes in existing solutions, ensuring stable and uniform coating thickness and improved storage stability, particularly for flat-angle wires.
Patent Information
- Application Number
- JP2023152399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Existing polyamic acid solutions used for coating insulated wires, especially flat-angle wires, face challenges with viscosity changes over time, particularly when stored at elevated temperatures, leading to inconsistent film thickness and reduced storage stability.
A polyamic acid solution with specific terminal structures, represented by general formulas (2) and (3), is developed, which maintains low viscosity and suppresses viscosity changes over time, ensuring uniform coating thickness and improved storage stability.
The solution achieves stable coating thickness and excellent tensile elongation, making it suitable for winding coating applications, particularly for flat-shaped wires, while maintaining high storage stability even at elevated temperatures.
Smart Images

Figure 2025044677000001 
Figure 2025044677000002 
Figure 2025044677000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solution containing polyamic acid (PAA), which is a polyimide (PI) precursor, and this solution can be suitably used as a coating solution for coating an insulated electric wire, such as a round wire, a rectangular wire, or a hexagonal wire, with a polyimide layer. [Background technology]
[0002] Polyamic acid solutions are often used to form polyimide layers with good mechanical properties and excellent electrical properties for coating insulated wires. In recent years, with the trend toward higher output, smaller size, and lower power consumption of electronic devices, it is required to be able to coat various wire shapes other than round wires. In particular, rectangular wire shapes can improve the coil occupancy rate, and allow for a larger current with a smaller volume than round wires (Patent Document 1). When forming an insulating layer on rectangular wires, the polyamic acid solution used as the coating material is required to have a high solids concentration but low viscosity in order to prevent the film thickness from fluctuating during coating and to form a uniform insulating coating with good productivity. In addition, Patent Document 2 shows a solution containing ester-terminated polyamic acid and diamine-terminated polyamic acid, and discloses that a polyimide resin with high mechanical strength can be realized by polymerizing the solution when heated while maintaining both high concentration and low viscosity. Furthermore, Patent Document 3 discloses a polyamic acid solution in which phthalic anhydride is used as an end-capping material in order to prevent a sudden increase in viscosity during the production of polyamic acid. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-288088 A [Patent Document 2] JP 2016-151020 A [Patent Document 3] JP 2013-28695 A Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, in the manufacturing process of insulated electric wires, the coating liquid is left in an environment of 40 to 50°C for a long time (several days) during coating, so it is necessary to minimize the change in viscosity over time. If the change in viscosity over time is large, a coating of the same thickness cannot be obtained stably. Furthermore, if the viscosity increases, defects are more likely to occur. These problems are particularly noticeable when coating electric wires with corners, such as rectangular wires. Therefore, there is a demand for a coating that does not change viscosity as much as possible in an environment of about 40°C, at least during the process.
[0005] However, the solution described in Patent Document 2 had poor storage stability and tended to increase in viscosity when stored for a certain period of time in a high-temperature environment. Therefore, in order to actually use these solutions, there were significant restrictions on their use, such as the need to introduce special equipment that provides a cooling function to the storage container for the coating liquid and the need to limit the length of each coating process.
[0006] Therefore, the present invention has been made to solve the above problems, and has an object to provide a polyamic acid solution which has a viscosity suitable for coating electric wires, exhibits good viscosity change over time, and exhibits high tensile elongation when formed into a film. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the inventors have found that the above problems can be solved by specifying the PAA terminal, and have thus completed the present invention. A PAA solution containing PAA and a solvent, wherein the molecular chain of the PAA has a repeating unit represented by general formula (1), and the PAA solution has, at one or both ends of the molecular chain of the PAA, a terminal structure represented by general formula (2) and a terminal structure represented by general formula (3). Here, the terminal structure represented by general formula (2) is 4 mol % or more and 12 mol % or less based on the amount of all aromatic acid dianhydride components, and the terminal structure represented by general formula (3) is 2 mol % or more and 8 mol % or less based on the amount of aromatic acid dianhydride. [ka] (In formula (1), R1 is a tetravalent organic group derived from an aromatic acid dianhydride component, R2 is a divalent organic group derived from an aromatic diamine component, and the repeating number n is an integer of 1 or more.) [ka] (In formula (2), R1 is a tetravalent organic group derived from an aromatic acid dianhydride component, and R3 is a monovalent organic group derived from a monovalent alcohol component.) [ka] (In formula (3), R4 is a divalent organic group derived from an acid anhydride component.) Effect of the Invention
[0008] The PAA solution of the present invention has a low viscosity at a given solid content concentration, and the change in viscosity over time is suppressed. Therefore, a coating with excellent thickness uniformity can be formed from this solution. Furthermore, as for the physical properties during the coating formation, the resulting coating has a tensile elongation sufficient for wire coating applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below.
[0010] The PAA solution used in the present invention contains PAA and an organic solvent. PAA has a molecular chain represented by the general formula (1) derived from an aromatic tetracarboxylic dianhydride component and an aromatic diamine component. [ka] Moreover, PAA has the terminal structures of general formula (2) and general formula (3) as its terminal structures. [ka] [ka]
[0011] The aromatic acid dianhydride component in PAA is not particularly limited, but can be pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, etc., among which PMDA is preferred. These may be used alone or in combination of two or more.
[0012] The aromatic diamine components in PAA include 4,4′-diaminodiphenyl ether (ODA), 2′-methoxy-4,4′-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2′-bis[4-(4-aminophenoxy)phenyl]propane, 2,2′-dimethyl-4,4′-diaminobiphenyl, 3,3′-dihydroxy-4,4′-diaminobiphenyl, 4,4′-diaminobenzanilide, bisanilinefluorene, 2,2-bis-[4-(3-amino phenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)]biphenyl, bis[4-(3-aminophenoxy)biphenyl, bis[1-(4-aminophenoxy)]biphenyl, bis[1-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]ether, bis [4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)]benzophenone, bis[4-(3-aminophenoxy)]benzophenone, bis[4,4′-(4-aminophenoxy)]benzanilide, bis[4,4′-(3-aminophenoxy)]benzanilide, 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[ 4-(3-aminophenoxy)phenyl]hexafluoropropane, 4,4'-methylenedi-o-toluidine, 4,4'-methylenedi-2,6-xylidine, 4,4'-methylene-2,6-diethylaniline, 4,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, 4,4'-diaminodiphenylethane, 3,3'-diaminodiphenylethane, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfide, 3,3'-diaminodiphenylsulfide, 4,4'-Diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 3,3-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, benzidine, 3,3'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 4,4"-diamino-p-terphenyl, 3,3"-diamino-p-terphenyl, m-phenylenediamine, p-phenylenediamine, 2,6-diaminopyridine, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, bis(p-aminocyclohexyl) Examples of the diisocyanate derivatives include bis(p-β-amino-t-butylphenyl)methane, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-t-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, and diisocyanate derivatives thereof. ODA is preferred because it can improve the flexibility of the resulting polyimide resin. These may be used alone or in combination of two or more. Furthermore, when ODA is combined with PMDA as an aromatic tetracarboxylic dianhydride, it is preferable because it provides a good balance between flexibility, heat resistance, and mechanical strength (tensile elongation).
[0013] The PAA solution of the present invention is obtained by polymerizing an acid component containing an aromatic acid dianhydride and a diamine component containing an aromatic diamine in a solvent. The solution viscosity of the PAA solution thus obtained is preferably 4 Pa·s or more and 15 Pa·s or less, and more preferably 8 Pa·s or more and 12 Pa·s or less. In particular, when applying to a rectangular wire, a sufficient thickness is required to insulate the corners, and for this purpose, it is preferable that the viscosity is controlled within the above range. Here, the numerical value of the solution viscosity is obtained by measuring the rotational viscosity at 30°C using a DVL-BII type digital viscometer (B type viscometer) manufactured by Tokimec Co., Ltd. Note that if the solution viscosity exceeds 15 Pa·s, the coating thickness may become too thick and drying may become difficult. Also, if the solution viscosity is less than 4 Pa·s, it may be difficult to obtain sufficient thickness uniformity, and insulation may not be guaranteed.
[0014] The PAA solution of the present invention has a good, small change in viscosity over time, and therefore when applied to a coating process for wire coating, the difference between the initial coating thickness and the final coating thickness is small, and therefore a PI-coated wire with a stable coating thickness can be obtained over the entire length of the wire. The viscosity change over time is measured by placing the solution in an airtight container and storing it at 40°C for 96 hours, and then calculating the absolute value of the rate of change compared to the solution viscosity before storage. The rate of change in viscosity over time is preferably 45% or less, and more preferably 30% or less. If it is more than 45%, a PI-coated wire with a stable PI thickness may not be obtained in the actual wire coating process.
[0015] In the PAA solution of the present invention, the solid content of PAA is not particularly limited, but can be adjusted to any concentration with an upper limit of about 30 mass %. When used for wire coating, a high concentration of about 25 to 30 mass % is preferable, and 26 to 28 mass % is more preferable.
[0016] The ratio of aromatic tetracarboxylic dianhydride to aromatic diamine is preferably 0.9 to 1.1 mol, more preferably 0.95 to 1.05 mol, of aromatic diamine per 1 mol of aromatic tetracarboxylic dianhydride. When the amount of aromatic diamine per 1 mol of aromatic tetracarboxylic dianhydride is less than 0.9 mol, or when the amount of aromatic diamine per 1 mol of aromatic tetracarboxylic dianhydride is more than 1.1 mol, the degree of polymerization does not increase and a PAA solution having a desired viscosity may not be obtained.
[0017] The PAA in the present invention must contain a terminal structure represented by general formula (2). This structure improves the physical properties when formed into a coating. The terminal structure of general formula (2) must be 4 mol % or more and 12 mol % or less based on the amount of all aromatic dianhydrides. If this structure is less than 4 mol %, the viscosity is high and the PAA is not suitable for use as a winding coating. If it exceeds 12 mol %, the viscosity is low and the PAA is not suitable for use as a winding coating.
[0018] The terminal structure represented by general formula (2) is introduced into PAA by using alcohol. As the alcohol, a monohydric one is preferable, and examples thereof include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-hexanol, 2-hexanol, 3-hexanol, 1-heptanol, 2-heptanol, 3-heptanol, 4-heptanol, 1-octanol, 2-octanol, 3-octanol, 4-octanol, cyclohexanol, phenol, benzyl alcohol, methylcyclohexanol, 2-methyl-3-butanol, 2-methyl-3-pentanol, 2-methyl-3-hexanol, and 2,4-dimethyl-3-pentanol. Among them, methanol, ethanol, and phenol are particularly preferable.
[0019] The PAA in the present invention must contain a terminal structure represented by general formula (3). This structure improves the viscosity time-dependent change of the PAA solution. The terminal structure represented by general formula (3) must be 2 mol % or more and 8 mol % or less based on the amount of aromatic dianhydride. If this structure is less than 2 mol %, a sufficient effect of improving storage stability cannot be obtained. Furthermore, if it exceeds 8 mol %, the breaking elongation in a tensile test when made into a film decreases, making it unsuitable for use as a winding coating.
[0020] The terminal structure represented by general formula (3) is introduced into PAA by using an acid anhydride. Examples of the acid anhydride include phthalic anhydride, maleic anhydride, succinic anhydride, hexahydrophthalic anhydride, 2,3-naphthalenedicarboxylic anhydride, and 1,8-naphthalenedicarboxylic anhydride. Among them, phthalic anhydride and maleic anhydride are particularly preferred.
[0021] In the PAA solution of the present invention, any solvent can be used as long as it dissolves PAA. Specifically, amide solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, 1,3-dimethyl-2-imidazolidinone, 3-methoxy-N,N-dimethylpropanamide, 3-methoxy-N,N-dibutylpropanamide, N,N-dimethylpropionamide, N,N-dibutylpropionamide, and hexamethylphosphoramide, lactone solvents include γ-butyrolactone, γ-valerolactone, δ-valerolactone, and ε-caprolactone, and other solvents include tetramethylurea and tetraethylurea. Among these, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), etc. can be particularly mentioned as suitable solvents, and these solvents can be used alone or as a mixture. Among these, NMP, DMAc, and mixtures thereof are preferred.
[0022] The reaction temperature during the production of the PAA solution is preferably −30 to 70° C., more preferably −15 to 60° C. In this reaction, the order of addition of the monomer, solvent, acid anhydride, and alcohol is not particularly limited and may be any order. The monomer may be added in portions.
[0023] If necessary, other known additives such as silane compounds such as silane coupling agents, pigments, fillers such as conductive carbon black and metal particles, abrasives, dielectrics, lubricants, crosslinking agents, surfactants, etc. may be added to the PAA solution of the present invention, provided that the effects of the present invention are not impaired. In addition, other polymers and solvents such as water-insoluble ethers, alcohols, ketones, esters, halogenated hydrocarbons, and hydrocarbons may be added to the PAA solution of the present invention, provided that the effects of the present invention are not impaired.
[0024] The surfactant is not particularly limited, but a nonionic surfactant, anionic surfactant, cationic surfactant, amphoteric surfactant, etc. can be used. Examples of the nonionic surfactant include ester type, ether type, and ester-ether type surfactants. Examples of the anionic surfactant include carboxylate type, sulfonate type, sulfate ester salt type, and phosphate ester salt type. Examples of the cationic surfactant include amine salt type and quaternary ammonium salt type. Examples of the amphoteric surfactant include carboxylate type, amino acid type, and betaine type.
[0025] Examples of the silane compound include amino-based, epoxy-based, chlorine-based, mercapto-based, alkyl-based, ureido-based, methacryl-based, vinyl-based, styryl-based, and cationic silane coupling agents.Specific examples include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxy ...ethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, Examples of suitable silane compounds include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and mixtures thereof. The addition of the silane compound can improve the adhesion of the PAA coating to the substrate when the coating is thermally cured. In this case, the amount of the silane compound added is preferably more than 5 ppm and less than 10,000 ppm relative to the mass of PAA.
[0026] The crosslinking agent is not particularly limited, but examples thereof include carbodiimide compounds and compounds having two or more thermally crosslinkable groups in the molecule, such as alkoxymethyl groups, methylol groups, epoxy groups, and oxetanyl groups.
[0027] If necessary, a polymer other than PAA may be added to the PAA solution as long as the effect of the present invention is not impaired. Examples of such polymers include polyamide, polycarbonate, polybutylene terephthalate, polyethylene terephthalate, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyamideimide, and polyimide.
[0028] A coating having excellent tensile properties can be obtained from the PAA solution of the present invention. When the breaking elongation of this PI film is measured at a thickness of 25 μm, it is preferable that the breaking elongation is 80% or more, and more preferably 100% or more. If it is less than 80%, it may become defective when used as a coating for electric wire windings. The PI film can be produced, for example, by applying the PAA solution to a substrate such as glass, drying, and thermally curing it.
[0029] Thus, the PAA solution of the present invention is particularly suitable for use in coating electric wires and cable electric wires because of its excellent coating properties and viscosity change over time. In addition to the use in coating electric wires, it can be used to manufacture, for example, heat-resistant insulating tape, heat-resistant adhesive tape, high-density magnetic recording base, capacitor, film for FPC (flexible printed circuit board), etc. In addition, it can be used to manufacture molding materials and molded products such as sliding members filled with fluororesin or graphite, structural members reinforced with glass fiber or carbon fiber, bobbins of small coils, sleeves, and terminal insulation tubes. It can also be used to manufacture laminate materials such as insulating spacers for power transistors, magnetic head spacers, spacers for power relays, and spacers for transformers. It can also be used to manufacture enamel coating materials for solar cells, low-temperature storage tanks, space insulation materials, space exterior wall materials, integrated circuits, and slot liners. It can also be used to manufacture ultrafiltration membranes, reverse osmosis membranes, and gas separation membranes. In addition, it can be used for components inside electronic devices such as flat panel displays (FPDs) such as liquid crystal displays (LCDs), plasma display panels (PDPs), and organic light-emitting displays (OLEDs), and flexible devices such as electronic paper. It can also be used for diaphragms and diaphragms inside speakers. It can also be used to manufacture heat-resistant threads, textiles, nonwoven fabrics, etc. EXAMPLES
[0030] The present invention will be described in detail below with reference to examples, but is not limited to these examples.
[0031] Raw materials and reactants may be referred to by the following abbreviations: Pyromellitic dianhydride··PMDA 4,4´-Diaminodiphenyl ether···ODA Methanol: MeOH Ethanol: EtOH Phenol...PhOH Phthalic anhydride ···PA Maleic anhydride ···MA N,N-Dimethylacetamide...DMAc Polyamic acid: PAA Polyimide...PI
[0032] The PAA solution was evaluated as follows.
[0033] (1) Measurement of film tensile elongation at break The tensile elongation at break of the film was measured under the following conditions according to JIS K7161. Specifically, the film was cut into a width of 10 mm and a length of 100 mm, and measured using an Intesco Precision Universal Material Tester Model 2020 manufactured by Intesco Corporation, with a chuck distance of 50 mm and a pulling speed of 20 mm / min. The measured values were evaluated according to the following criteria as to whether they could be used for winding coating applications. ○: 80% or more ×: Less than 80%
[0034] (2) Viscosity measurement of PAA solution The viscosity of the PAA solution was measured as a rotational viscosity at 30° C. using a DVL-BII type digital viscometer (B type viscometer) manufactured by Tokimec Co., Ltd. The measured values were evaluated according to the following criteria. ◎:8Pa·s or more and 12Pa·s or less ○: 4 Pa·s or more but less than 8 Pa·s, or 12 Pa·s or more but less than 15 Pa·s ×: Less than 4 Pa·s or greater than 15 Pa·s
[0035] (3) Evaluation of viscosity change over time of PAA solution The PAA solutions prepared in each of the Examples and Comparative Examples were placed in a sealed container, and the solution viscosity after storage at 40° C. for 96 hours was measured. The rate of change relative to the solution viscosity before storage was calculated and evaluated as follows. ◎: The rate of change (absolute value) is 30% or less ○: The rate of change (absolute value) is greater than 30% and less than or equal to 45% ×: The rate of change (absolute value) is greater than 45%.
[0036] <Example 1> In a glass reaction vessel, ODA (0.70 mol) and dehydrated DMAc (700 g) were added under a nitrogen atmosphere and stirred to dissolve the ODA. While cooling this solution to below 30°C with a jacket, MeOH (0.056 mol, 8 mol% of PMDA) was added, followed by gradually adding PMDA (0.70 mol), followed by gradually adding PA (0.014 mol, 2 mol% of PMDA), and then polymerizing at 70°C for 120 minutes to obtain a PAA solution (A-1) with a solution viscosity of 13 Pa·s at 30°C and a PAA solid content of 27 mass%. The viscosity change over time of A-1 was evaluated, and the change rate was 40%. Next, A-1 was applied to the surface of a 3 mm thick glass substrate using a table coater, dried at 100°C for 10 minutes, and then heated to 350°C at a heating rate of 2°C / min under a nitrogen gas flow to thermally cure the PAA coating. The PI film had a thickness of 25 μm. The tensile elongation at break of the PI film was measured and found to be 110%.
[0037] <Examples 2 to 8> PAA solutions (A-2 to A-10) were obtained in the same manner as in Example 1, except that the types and ratios of the alcohol component and the acid anhydride component were changed as shown in Table 1. The solution viscosity at 30°C and the viscosity change over time of these varnishes were measured and evaluated, and the results are shown in Table 1. Next, PI films with a thickness of 25 μm were produced in the same manner as in Example 1. The tensile elongation at break of these PI films was measured, and the results are shown in Table 1.
[0038] <Comparative Examples 1 to 7> PAA solutions (B-1 to B-9) were obtained in the same manner as in Example 1, except that the types and ratios of the alcohol component and the acid anhydride component were changed as shown in Table 1. The solution viscosity at 30°C and the viscosity change over time of these varnishes were measured and evaluated, and the results are shown in Table 1. Next, PI films with a thickness of 25 μm were produced in the same manner as in Example 1. The tensile elongation at break of these PI films was measured, and the results are shown in Table 1.
[0039] <Comparative Example 8> A PAA solution was prepared based on Example 1 of Patent Document 2. That is, ODA (1.71 mol) and dehydrated DMAc (2140 g) were put into a glass reaction vessel under a nitrogen atmosphere and stirred to dissolve ODA. PMDA (1.79 mol) was added to this solution, and then EtOH (0.34 mol, 19 mol% of the PMDA put in immediately before) was added and stirred at 70°C for 120 minutes to carry out a polymerization reaction. Thereafter, ODA (0.81 mol) and PMDA (0.72 mol) were gradually added, and the polymerization reaction was carried out at 70°C for 120 minutes to obtain a PAA solution (B-10) with a solution viscosity of 15 Pa·s at 30°C and a PAA solid content concentration of 30 mass%. The solution viscosity at 30°C and the viscosity change over time of the varnish of B-10 were measured and evaluated, and the results are shown in Table 1. Next, a PI film with a thickness of 25 μm was produced in the same manner as in Example 1. The tensile elongation at break of these PI films was measured, and the results are shown in Table 1.
[0040] [Table 1]
[0041] The PAA Solutions A-1 to A-10 obtained in Examples 1 to 10 all had good viscosity, the film properties were good, and the viscosity change of the solution over time was small. In contrast, the PAA solutions B-1 to B-10 obtained in Comparative Examples 1 to 10 had the following problems, respectively. B-1: Because MeOH was not added, the viscosity was high at 60 Pa s. Because PA was not added, the viscosity change rate over time was poor at 70%. B-2: No PA was added, resulting in a poor viscosity change rate of 70%. B-3: Only 1 mol % of PA was added, resulting in a poor viscosity time-dependent change rate of 50%, making the material unsuitable for use in the winding coating process. B-4: Since MeOH was not added, the viscosity was high at 35 Pa·s and the elongation at break was low at 60%. B-5: Since MeOH is not added, the viscosity is high at 30 Pa·s and the elongation at break is low at 50%. B-6: Since MeOH was not added, the viscosity was high at 25 Pa·s and the elongation at break was low at 50%. B-7···MeOH was added at only 2 mol % and thus the viscosity was 20 Pa·s, which was unsuitable for use as a wire coating. B-8···MeOH was added in an excessive amount (14 mol%), resulting in a viscosity of 2 Pa·s, which is unsuitable for use as a wire coating. B-9: PA was added in an excessive amount (10 mol %), resulting in a low breaking elongation of 60%. B-10: No PA is added, so the viscosity change rate over time is poor at 70%. [Industrial Applicability]
[0042] The PAA solution of the present invention has a high concentration and a low viscosity, and also provides good coating properties and has excellent storage stability, making it suitable for use in coating winding wires, particularly for coating rectangular wires.
Claims
[Claim 1] A PAA solution containing polyamic acid (PAA) and a solvent, wherein the molecular chain of the PAA has a repeating unit represented by general formula (1), and the PAA solution has a terminal structure represented by general formula (2) and a terminal structure represented by general formula (3) at one or both ends of the molecular chain of the PAA. Here, the terminal structure represented by general formula (2) is 4 mol % or more and 12 mol % or less based on the amount of all aromatic acid dianhydride components, and the terminal structure represented by general formula (3) is 2 mol % or more and 8 mol % or less based on the amount of aromatic acid dianhydride. 【Chemistry 1】 (In formula (1), R 1 is a tetravalent organic group derived from an aromatic dianhydride component, R 2 is a divalent organic group derived from an aromatic diamine component, and the repeating number n is an integer of 1 or more. 【Chemistry 2】 (In formula (2), R 1 is a tetravalent organic group derived from an aromatic dianhydride component, R 3 is a monovalent organic group derived from a monohydric alcohol component.) 【Chemistry 3】 (In formula (3), R 4 is a divalent organic group derived from an acid anhydride component.
Citation Information
Patent Citations
Wire for coil and coil fabricated thereby
JP2007288088A
Polyimide resin vanish, and insulated electric wire, electric coil and motor using the same
JP2013028695A
Polyimide coating material and insulated wire
JP2016151020A